Empat Pilar Transformasi Digital yang Mengubah Lanskap Bisnis Indonesia Menuju Era Inovasi dan Pertumbuhan Berkelanjutan - Yohana Maritza Fatma Ayu Widyoputri; Anik Avitasari (sekolah Tinggi Ilmu Ekonomi Dharma Putra Semarang, 2026)
This study discusses the four pillars of digital transformation that are currently changing the business landscape in Indonesia, namely the digital ecosystem, digital twin technology, open innovation framework, and agile transformation. This study aims to identify and explain the key concepts underlying digital business innovation and its impact on business development in the modern era. The method used is a literature study with descriptive analysis of various primary and secondary sources related to digital innovation. The findings show that the application of these four pillars drives operational efficiency, increased cross-sector collaboration, accelerated product and service innovation, and increased business competitiveness. The implications of this study emphasize the importance of adopting a holistic digital strategy for companies to survive and thrive in an increasingly competitive and dynamic market. By understanding and implementing these pillars of digital transformation, Indonesian businesses can leverage the latest technologies to create innovative and sustainable business models.